2017
DOI: 10.1177/1528083717720203
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis on tensile strength of dry and moisture absorbed hybrid kenaf/glass polymer composites

Abstract: Economic and environmental concerns lead the researchers toward development of sustainable and renewable materials of which reinforced composites are part of. The abundantly available natural fibers have attracted the researchers to study their performance as reinforcements and feasibility for making automobile components. The performance of composite materials is mainly assessed through their mechanical properties. However, natural fibers to date were mainly used as reinforcements to create bulk composite com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Hybrid fiber composites development aims to produce a product with performance characteristics that combine each component's positive attributes. By mixing two types of fiber, one fiber could complement what is lacking in the other fiber [116,117]. Several works have been reported on treated and hybrid fiber composites by using natural fiber and synthetic fiber.…”
Section: Thermal Degradation Stability Performance Of Hybrid Natural Fiber-reinforced Thermoplastic Compositesmentioning
confidence: 99%
“…Hybrid fiber composites development aims to produce a product with performance characteristics that combine each component's positive attributes. By mixing two types of fiber, one fiber could complement what is lacking in the other fiber [116,117]. Several works have been reported on treated and hybrid fiber composites by using natural fiber and synthetic fiber.…”
Section: Thermal Degradation Stability Performance Of Hybrid Natural Fiber-reinforced Thermoplastic Compositesmentioning
confidence: 99%
“…This result implies that the location of the high strength and the low strength fiber decides the mechanical properties of polymer laminate. Although numerous studies have been reported on mechanical characterization of various natural fibers as a reinforcing agent for the polymeric matrix, 68,27 the research reports on the mechanical properties of basalt and flax intertwined polymer laminate have been rather limited. The literature study indicates the need for polymer composite laminates with sufficient high mechanical and damping characteristics under dynamic loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Praveenkumar et al. [13] analysed the combined effects of mercerisation, hybridisation and incorporation of fly ash fillers on the properties of kenaf/glass polymer composites. They found that 10 wt% of fly ash particles considerably improved the tensile strength of polymer composites.…”
Section: Introductionmentioning
confidence: 99%